THE ROLE OF MICRONIZED PROGESTERONE IN THE PREVENTION OF PRETERM BIRTH IN WOMEN WITH CERVICAL LENGTH GREATER THAN 2.5 CM - AKHTAR , T; REHMAN , T; MANSOOR , A (Biological and Clinical Sciences Research Journal, 2023)
Preterm birth, defined as the delivery of a baby before 37 weeks of gestation, remains a significant public health concern globally due to its association with adverse neonatal outcomes and long-term health implications. The study’s main objective is to find the role of Micronized progesterone in preventing preterm birth in women with cervical length greater than 2.5 cm. This prospective study was conducted in DHQ Teaching Hospital Gujranwala in 2023. Data was collected from 120 female patients. The study population comprises pregnant women with a singleton gestation, cervical length greater than 2.5 cm, and no history of preterm birth. Informed consent is obtained from all participants, and ethical approval is secured from relevant institutional review boards. Micronized progesterone demonstrated a 5% preterm birth rate compared to 10% in the control group (p=0.03). Adherence was high (92%), and adverse events were mild. Birth weight increased in the intervention group. Subgroup analysis revealed consistent preventive effects across various cervical length strata. It is concluded that micronized progesterone supplementation among women with cervical length > 2.5 cm shows promise in reducing preterm birth rates. The safety profile and adherence support its feasibility in routine prenatal care.